2019
DOI: 10.29252/jhc.20.4.301
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Emotional Self-Regulatory Model on Improving the Quality of Life in Multiple Sclerosis Patients

Abstract: Background & objectives: Considering the prevalence of psychological problems in patients with multiple sclerosis (MS), some reports have recognized the effectiveness of emotional self-regulation model prior to conventional therapies in these patients. The aim of this study was to investigate the effectiveness of emotional self-regulation model to improve the components of life quality in MS patients. Methods: This study was a semi-experimental with pre-and post-test, and control group. The quality of life tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…34 Moreover, the validity of the Farsi version of this resilience scale has been tested and also verified, and the reliability of the scale was reported equal to a Cronbach's alpha of 0.87. 35…”
Section: Methodsmentioning
confidence: 99%
“…34 Moreover, the validity of the Farsi version of this resilience scale has been tested and also verified, and the reliability of the scale was reported equal to a Cronbach's alpha of 0.87. 35…”
Section: Methodsmentioning
confidence: 99%
“…A score of 0 to 33 indicates low resilience, 34 to 67 indicates average resilience, and above 68 indicates high resilience [ 22 ]. The scale's reliability has been verified by a Cronbach’s alpha of 0.91 in Iran [ 23 ]. Cronbach’s alpha for this questionnaire in the present study was 0.93.…”
Section: Measurementmentioning
confidence: 99%
“…Fayand et al (2019) reported the face and content validity and reliability of the scale to be satisfactory. Reliability of the Cronbach's alpha of the scale was 0.82 (Fayand et al, 2019).…”
Section: Connor-davidson Resilience Scalementioning
confidence: 95%
“…The score range is between 0 and 100, with higher scores indicating greater resilience (Connor and Davidson, 2003). Fayand et al (2019) reported the face and content validity and reliability of the scale to be satisfactory. Reliability of the Cronbach's alpha of the scale was 0.82 (Fayand et al, 2019).…”
Section: Connor-davidson Resilience Scalementioning
confidence: 99%